Clinical utility of existing and second-generation interferon-γ release assays for diagnostic evaluation of tuberculosis: an observational cohort study. Issue 2 (February 2019) - Whitworth, Hilary S; Badhan, Amarjit; Boakye, Aime A; Takwoingi, Yemisi; Rees-Roberts, Melanie; Partlett, Christopher; Lambie, Heather; Innes, John; Cooke, Graham; Lipman, Marc; Conlon, Christopher; Macallan, Derek; et al.
Summary: Background: The clinical utility of interferon-γ release assays (IGRAs) for diagnosis of active tuberculosis is unclear, although they are commonly used in countries with a low incidence of tuberculosis. We aimed to resolve this clinical uncertainty by determining the accuracy and utility of commercially available and second-generation IGRAs in the diagnostic assessment of suspected tuberculosis in a low-incidence setting. Methods: We did a prospective cohort study of adults with suspected tuberculosis in routine secondary care in England. Patients were tested for Mycobacterium tuberculosis infection at baseline with commercially available (T-SPOT. TB and QuantiFERON-TB Gold In-Tube [QFT-GIT]) and second-generation (incorporating novel M tuberculosis antigens) IGRAs and followed up for 6–12 months to establish definitive diagnoses. Sensitivity, specificity, positive and negative likelihood ratios, and predictive values of the tests were determined. Findings: Of the 1060 adults enrolled in the study, 845 were included in the analyses and 363 were diagnosed with tuberculosis. Sensitivity of T-SPOT. TB for all tuberculosis diagnosis, including culture-confirmed and highly probable cases, was 81·4% (95% CI 76·6–85·3), which was higher than QFT-GIT (67·3% [62·0–72·1]). Second-generation IGRAs had a sensitivity of 94·0% (90·0–96·4) for culture-confirmed tuberculosis and 89·2% (85·2–92·2) when including highly probable tuberculosis, giving a negative likelihood ratio for all tuberculosis cases of 0·13 (95% CI 0·10–0·19). Specificity ranged from 86·2% (95% CI 82·3–89·4) for T-SPOT. TB to 80·0% (75·6–83·8) for second-generation IGRAs. Interpretation: Commercially available IGRAs do not have sufficient accuracy for diagnostic evaluation of suspected tuberculosis. Second-generation tests, however, might have sufficiently high sensitivity, low negative likelihood ratio, and correspondingly high negative predictive value in low-incidence settings to facilitate prompt rule-out of tuberculosis. Funding: National Institute for Health Research.